Pengembangan Lanjut Penerapan Bates Method Pada Aplikasi Mobile Berbasis Virtual Reality Menggunakan Metode Pengembangan Personal Extreme Programming - Abdul Ghoniy Nur Chasana; Komang Candra Brata; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
A common solution for myopia sufferers is to wear glasses. However, glasses are not for curing vision, but they only help sufferers to see more clearly. In 1920 Dr. William Horatio Bates invented a practical and free method called the Bates method, this method can be done by everyone to cure minus eye without having to use tools. The Bates method is implemented into an application called Bates EyeCare using virtual reality technology. Bates EyeCare simulates eye muscle training in a virtual world by using objects in that world as a training reference. By utilizing the personal extreme programming development method aimed at developing fast and concise individual applications, 2 iterations with 1 iteration focused on developing eye sports methods in the virtual world using Unity3d with real processing time of 30 hours 7 minutes, faster 5 7 hours from the estimated development time, while the development in iteration 2 focuses on implementing the unity module from the results of iteration 1 on Android Studio so that the virtual world can be used on the Android mobile platform with real processing time is 20 hours 40 minutes, 20 minutes faster than the estimate development time. User acceptance testing was conducted on 4 respondents with a final score of 5,582, which stated that the overall user was of the opinion Agree that the system has succeeded in meeting the needs of the user.